IMPLEMENTATION OF DECISION SUPPORT SYSTEM(DSS) FOR BUDGET PLANNING AND CONTROL: BRIDGING GOOD GOVERNANCE AND UNQUALIFIED OPINIONS (WTP) IN LOCAL GOVERNMENT - Husmaruddin, Husmaruddin; Mallu, Satriawaty; Salju, Salju (Nusantara Hasana Journal, 2025)
This research evaluates how the implementation of a Decision Support System (DSS) can improve good governance and the achievement of WTP in regional finance, with implications for policy design and public resource management. Using a phased mixed design, this study first measures the impact of DSS adoption on budget accuracy, expenditure control, and WTP achievement through panel data in several districts/cities. Furthermore, policy-oriented case analysis was conducted to identify governance mechanisms, data governance practices, and capacity building needs that enable the sustainable use of DSS. Data sources included local government budget reports, Supreme Audit Agency (BPK) audit reports, budget documents, and interviews with stakeholders. Metrics included DSS maturity (level of integration, data quality, analytical coverage), deviation reduction, control strength, and WTP status. The findings show that DSS maturity is positively related to budget deviation reduction and increased alignment between planning and implementation, thereby increasing the chances of achieving WTP. Policy implications include a DSS governance framework; ensuring data interoperability in the regional IT ecosystem; capacity investment; and aligning DSS outputs with the audit process. Limitations relate to data availability and constraints in transferring findings across regional contexts. This paper contributes to the public financial management literature by linking advanced information systems to governance quality and external reporting standards, and offers a roadmap for local governments seeking to improve financial transparency and accountability